Assessing Levels of Empathy among Undergraduate Medical Students: Results of a Cross-Sectional Study Conducted in a Medical College in Sohar, Oman - Qureshi, Abdul Hafeez; AlHabsi, Ramitha; Alghatrifi, Sharifa; Alhabsi, Sara; Alarrasi, Omnia (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: Empathy is an essential aspect of communication skills for physicians, especially primary care physicians. The study aims to explore the empathy scores among medical students at different stages of medical training and to analyze the effect of gender and career choice on the empathy scores of medical students. Methodology: A cross-sectional study was conducted from October 2021 to January 2022 in a medical college in Sohar, Oman. All the students were eligible to participate in this study. Simple random sampling was employed, and participants were administered a 20-item Jefferson Scale of Empathy-Student (JSE-S) Version. Data were analyzed using SPSS version 22. Mean and standard deviation were reported for continuous variables. Subgroup comparisons were conducted using t-test and ANOVA. Results: Out of 424 participants, the majority were female (n=390,92%), and over half of the students (56%) were less than 22 years of age. The mean empathy score of students on the JSE-S scale was 104.6 ± 17.43 (range: 37-140). Subgroup analysis revealed that males had a slightly high score on JSE-S (male: 105.7+14.56, female: 104.5+17.6, p-0.23). Empathy scores showed an increasing trend as the student progressed through medical school (6th year: 106.2+16.16). Empathy scores were almost similar for students who had preferred people or procedure-oriented fields as their career pathway (p-0.59). Conclusion: The study reflects the need to include empathy in teaching communication skills to medical students as an integral part of the medical school curriculum, which could assist them in becoming compassionate physicians and increasing patient satisfaction.